Pemberdayaan Masyarakat Melalui Program Biogas - Indah Wulandari Chabib; Aliyudin Aliyudin; Ratna Dewi (Jurusan Pengembangan Masyarakat Islam, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Dj, 2021)
This paper aims to determine the community empowerment carried out by Yayasan Rumah Energi in the Padamukti Village in empowering the community to be able to process cow dung which was originally thrown into the river which resulted in pollution, then processed into biogas. The exsistence of this community empowerment helps the community to reduce the environmental pollution that results from the dumping of cow dung into the river, besides having an impact on the community economy by using biogas. This study uses qualitative research using descriptive methods. This data collection uses observation techniques, interview, and study documentation. This analysis in this study uses data reduction, presentation, and verivication. The result of this study show how the empowerment carried out bye Yayasan Rumah Energi and the community by processing cow dung through the biogas program so that the community can have a clean environment and provide economic improvement.